Natural convective mass transfer in short vertical annuli - Rai B.N.; Upadhyay S.N. (My University, 2025)
Equations for natural convective mass transfer in short vertical annuli are proposed using equivalent diameter as the characteristic length parameter. Data for annuli of large gap width (de/L0.62) are correlated by the equation. © 1985, Taylor & Francis Group, LLC. All rights reserved.